Probiotics for Parkinson's disease: Current evidence and future directions - Tan, Ai Huey (JGH Open, 2020)
The gut–brain axis is a hot topic in Parkinson's disease (PD). It has been postulated that gut pathogens and dysbiosis can contribute to peripheral inflammatory states or trigger downstream metabolic effects that exacerbate the neurodegenerative process in PD. Several preclinical and clinical studies have demonstrated disrupted intestinal permeability, intestinal inflammation, altered gut microbiome, and reduced fecal short‐chain fatty acids in PD. In this regard, microbial‐directed therapies such as probiotics are emerging as potential therapeutic options. Probiotic supplementation is postulated to confer a variety of health benefits due to the diverse functions of these live microorganisms, including inhibition of pathogen colonization, modulation/“normalization” of the microbiome and/or its function, immunomodulatory effects (e.g. reducing inflammation), and improved host epithelial barrier function. Interestingly, several PD animal model studies have demonstrated the potential neuroprotective effects of probiotics in reducing dopaminergic neuronal degeneration. Notably, two randomized placebo‐controlled trials have provided class I evidence for probiotics as a treatment for constipation in PD. However, the effects of probiotics on other PD aspects, such as motor disability and cognitive function, and its long‐term efficacy (including effects on PD drug absorption in the gut) have not been investigated adequately. Further targeted animal and human studies are also warranted to understand the mechanisms of actions of probiotics in PD and to tailor probiotic therapy based on individual host profiles to improve patient outcomes in this disabling disorder.